The spina bifida: Management and outcome - (:unkn) unknown (Springer Milan, 2008)
The evolution of technology has made new surgical techniques available for the treatment of diseases associated with the spina bifida malformation, and this is especially true in hydrocephalus and fetal surgery. The progress in this last field and in prenatal diagnosis have raised the significant problem of the effectiveness and usefulness of in utero surgical treatment of the malformation, that are extensively discussed in this volume. Also the clinical situations that can be seen in adolescents or young adults with spina bifida, including sexuality and pregnancy, are highlighted. Aim of this book is to promote a multidisciplinary approach to spina bifida, providing the three main specialists categories involved - neurosurgeons, orthopaedic surgeons, and urologists - with an updated overview of surgical approaches and with a concise reference that explains the main clinical problems to be faced in everyday clinical practice. © Springer-Verlag Italia 2008.